Pengaruh Ukuran Perusahaan, Leverage, dan Profitabilitas Terhadap Nilai Perusahaan - Winda Agustina; H. Sissah (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of firm size, leverage, and profitability on firm value in PT Aneka Tambang (Persero) Tbk during the 2017–2024 period. The research employs a quantitative approach using multiple linear regression analysis with secondary data obtained from the official website of the Indonesia Stock Exchange (IDX). The independent variables consist of firm size, leverage, and profitability, while the dependent variable is firm value measured using the Price to Book Value (PBV) ratio. The results indicate that, partially, firm size has no significant effect on firm value, meaning that the company’s asset scale does not determine investor confidence or market valuation. Leverage also has no significant effect on firm value, showing that the use of debt does not directly affect investor perceptions. Similarly, profitability measured by Return on Assets (ROA) does not significantly influence firm value, indicating that the company’s profitability level has not provided a strong positive signal to investors. Simultaneously, the three variables firm size, leverage, and profitability also have no significant effect on firm value. The coefficient of determination (Adjusted R²) which means that only 4.3% of the variation in firm value can be explained by these three variables, while the remaining 95.7% is influenced by other factors outside the model such as macroeconomic conditions, commodity prices, and government policies that affect the mining industry’s performance.